Histological exploration of Graafian and atretic follicles of buffalo ovary: A seasonal study - Sasan, Jasvinder Singh; Uppal, Varinder; Bansal, Neelam; -, Anuradha (Buffalo Bulletin, 2016)
The present research work was conducted to study distribution of Graafian and atretic follicles in buffalo ovary during different seasons of year. For this purpose, 100 ovaries of adult Murrah buffaloes during different seasons (20 in each season) of year viz; winter (November - January), spring (February - March), summer (April - June), rainy (July - August) and autumn (September - October) were collected from slaughter house. The paraffin sections of 10 µm were cut and every 20th section was stained with hematoxylin and eosin. In present study, two types of follicles were observed viz. young and mature Graafian follicles. Highest number of normal follicles was during autumn season whereas lowest number of normal follicles was during summer season. The most common type of atresia was antral. The ratio of normal to atretic follicle was maximum in summer (1: 3.10) and minimum in autumn season (1: 2.19).